Mixed pain: clinical practice recommendations - Varrassi, Giustino; Farì, Giacomo; Narvaez Tamayo, Marco Antonio; Gomez, Maria Patricia; Guerrero Liñeiro, Aura Marixa; Pereira, Carla Leal; Samy Aziz, Ezzat; Gharibo, Christopher; Kaye, Alan D.; Garcia-Larrea, Luis; Moka, Eleni; Król, Andrzej; et al. (Frontiers in Medicine, 2025)
Mixed pain, defined by the concurrent involvement of nociceptive, neuropathic, and sometimes nociplastic mechanisms, poses a significant diagnostic and therapeutic challenge within modern pain medicine. This complex pain phenotype is increasingly recognized as a prevalent and burdensome clinical entity, yet it remains substantially underdiagnosed and sub-optimally managed across diverse healthcare settings. Epidemiological data indicate that mixed pain affects a substantial proportion of patients with chronic pain syndromes and is consistently associated with more severe symptomatology, prolonged pain duration, functional impairment, diminished quality of life, and escalated healthcare resource utilization compared to pain of a single mechanism. In response to this unmet clinical need, the present recommendations aim to provide a structured, evidence-informed framework for the diagnosis and management of mixed pain. Developed through a rigorous process involving systematic literature review and multidisciplinary expert consensus, this document emphasizes the importance of mechanism-based therapeutic strategies tailored to the individual patient’s pain profile. Central to the approach is the implementation of multimodal and interdisciplinary care models that address the biological, psychological, and functional dimensions of mixed pain. These recommendations are intended for a broad spectrum of healthcare professionals, including primary care physicians, pain specialists, neurologists, oncologists, physiatrists, nurses, pharmacists, physical and occupational therapists, and clinical psychologists. The target population encompasses patients affected by mixed pain conditions such as chronic low back pain with radiculopathy, cancer-related pain, persistent post-surgical pain, and osteoarthritis complicated by central sensitization. By facilitating accurate diagnosis and integrated treatment planning, these recommendations seek to advance clinical practice, reduce the burden of mixed pain, and enhance patient-centered outcomes. This guidance aims to transform mixed pain care by promoting mechanism-based, multidisciplinary strategies with direct clinical applicability.